The marked and rapid therapeutic effect of tofacitinib in combination with subcutaneous methotrexate in a rheumatoid arthritis patient with poor prognostic factors who is resistant to standard disease-modifying antirheumatic drugs and biologicals: A clinical case - N. V. Demidova; E. L. Luchikhina; D. E. Karateev (Современная ревматология)
Today, it is generally accepted that it is necessary to achieve clinical remission in rheumatoid arthritis (RA) or as minimum a low disease activity. The paper describes a clinical case of a female patient diagnosed with RA who was observed to have inefficiency of standard disease-modifying antirheumatic therapy with methotrexate 25 mg/week, secondary inefficiency of tumor necrosis factor-α inhibitors (adalimumab), and inefficiency/poor tolerance of the interlukin-6 receptor antagonist tocilizumab. This determined the need to use fofacitinib (TOFA), a drug with another mechanism of action. TOFA is the first agent from a new group of immunomodulatory and anti-inflammatory drugs, intracellular kinase inhibitors. Disease remission could be achieved during therapy with TOFA, which enables one to consider this synthetic drug as a therapy option that potentially competes with therapy with biologicals.